Система автоматизации имитационного моделирования последовательных вероятностных технологических процессов производства - Клименко, А.В.; Максимей, И.В.; Смородин, В.С. (Інститут програмних систем НАН України, 2008)
It is considered probabilistic technological proc-esses of manufacture with non-standard sequence of change of conditions. Features of consecutive probabilistic processes as object of imitation, structure and structure of system of modeling are stated. The technology of use of system of modeling is offered and prospects of its application are certain.